Gibberellin–Abscisic Acid Balances during Arbuscular Mycorrhiza Formation in Tomato - Martín-Rodríguez, José A.; Huertas, Raúl; Ho-Plágaro, Tania; Ocampo, Juan A.; Turečková, Veronika; Tarkowská, Danuše; Ludwig-Müller, Jutta; García-Garrido, José M. (Frontiers in Plant Science, 2016)
Plant hormones become appropriate candidates for driving functional plant mycorrhization programs, including the processes that regulate the formation of arbuscules in Arbuscular Mycorrhizal (AM) symbiosis. Here, we examine the role played by ABA/GA interactions regulating the formation of AM in tomato. We report differences in ABA and GA metabolism between control and mycorrhizal roots. Active synthesis and catabolism of ABA occur in AM roots. GAs level increases as a consequence of a symbiosis-induced mechanism that requires functional arbuscules which in turn is dependent on a functional ABA pathway. A negative interaction in their metabolism has been demonstrated. ABA attenuates GA-biosynthetic and increases GA-catabolic gene expression leading to a reduction in bioactive GAs. Vice versa, GA activated ABA catabolism mainly in mycorrhizal roots. The negative impact of GA3 on arbuscule abundance in wild-type plants is partially offset by treatment with ABA and the application of a GA biosynthesis inhibitor rescued the arbuscule abundance in the ABA-deficient sitiens mutant. These findings, coupled with the evidence that ABA application leads to reduce bioactive GA1, support the hypothesis that ABA could act modifying bioactive GA level to regulate AM. Taken together, our results suggest that these hormones perform essential functions and antagonize each other by oppositely regulating AM formation in tomato roots.